Labour market concentration, wages and job security in Europe - Bassanini, Andrea (2023)
We investigate the impact of labour market concentration on two dimensions of job quality, namely wages and job security. We leverage rich administrative linked employer-employee data from Denmark, France, Germany, Italy, Portugal and Spain in the 2010s to provide the first comparable cross-country evidence in the literature. We show that the elasticities of wages with respect to labour market concentration are strikingly similar across countries. Increasing labour market concentration by 10% reduces wages by 0.19% in Germany, 0.22% in France, 0.25% in Portugal and 0.29% in Denmark. We find greater elasticities for job security. An increase in labour market concentration by 10% reduces the probability of being hired on a permanent contract by 0.46% in France, 0.51% in Germany and 2.34% in Portugal. In Italy and Spain, while not affecting this probability, labour market concentration has a strong negative effect on conversions to a permanent contract once hired on a temporary one. Using German and Portuguese data, we provide suggestive evidence that the similarity of our wage elasticities across countries and the greater sensitivity of job security to labour market concentration may be explained by the fact that sector-level collective bargaining is dominant in the countries we study and that it sets wages but usually not contract type.